ENHANCING CRITICAL THINKING FOR YOUNG EFL STUDENTS USING ANECDOTES - Kamola Daniyarova; Hannah Landers (Western European Studies, 2023)
Educators know that students should be taught to be critical thinkers starting at a young age. What can be unclear is how to define critical thinking, how to teach critical thinking, and how to assess if critical thinking has been taught. Additionally, when the student population is composed of young English as a foreign language (EFL) learners, another component is added: how can critical thinking be incorporated into learning another language. This paper will discuss a working definition of what critical thinking is within the context of primary education in Uzbekistan and methods for teaching critical thinking.
Keywords: definition; education; composed; language